SISTEM INFORMASI DASHBOARD MONITORING C/N PADA PRODUK SCPC DI PT. PI [DASHBOARD INFORMATION SYSTEM FOR C/N MONITORING ON SCPC PRODUCTS AT PT. PI] - Chuan Pratama; Junita Junita (Universitas Pelita Harapan, 2024)
SCPC (Signal Carrier Per Carrier) is a priority VSAT service that requires continuous frequency signal monitoring to ensure network stability. Currently, this monitoring is performed using a web-based decimator device. However, the monitoring data still requires manual processing to create reports and analyses, which is inefficient and time-consuming. This study developed a web-based dashboard monitoring system that automates the processing of C/N (Carrier to Noise) data for SCPC products at PT. PI. The system was tested using a task scheduler for 14 hours with 30-minute intervals, recording a longest processing time of 16.665 seconds with 11,812 data points, 60.6% RAM usage, and 36.9% CPU usage, and a shortest processing time of 4.026 seconds with 3,546 data points, 53.9% RAM usage, and 39.7% CPU usage. The proposed web application successfully displays historical graphs, total remote counts, databases, top 10 under C/N, tables, and reports, as initially designed. The average dashboard loading time to complete data display is approximately 9.894 seconds. This system is expected to improve the efficiency of SCPC monitoring and provide faster, more accurate reporting.Bahasa Indonesia Abstract:SCPC (Signal Carrier Per Carrier) adalah layanan VSAT prioritas yang memerlukan monitoring sinyal frekuensi secara terus-menerus untuk memastikan kestabilan jaringan. Saat ini, monitoring dilakukan melalui perangkat decimator berbasis web; namun, pengolahan data monitoring menjadi laporan dan analisis masih harus dilakukan secara manual, yang tidak efisien dan memakan waktu. Penelitian ini mengembangkan sistem dashboard monitoring berbasis web yang mampu mengotomatisasi pengolahan data C/N (Carrier to Noise) pada produk SCPC di PT. PI. Sistem ini diuji menggunakan task scheduler selama 14 jam dengan interval 30 menit, di mana waktu proses terlama tercatat 16,665 detik dengan 11.812 data, penggunaan RAM 60,6%, dan CPU 36,9%; sementara waktu tercepat adalah 4,026 detik dengan 3.546 data, penggunaan RAM 53,9%, dan CPU 39,7%. Aplikasi web berhasil menampilkan grafik historis, total remote, basis data, top 10 di bawah C/N, tabel, dan laporan sesuai desain awal. Waktu rata-rata yang dibutuhkan dashboard untuk memuat data hingga selesai adalah sekitar 9,894 detik. Pengembangan sistem ini diharapkan dapat meningkatkan efisiensi monitoring SCPC dan memberikan laporan yang lebih cepat dan akurat.